INFLUENCE OF THE TYPE OF ADHESIVE ON THE PHYSICO-MECHANICAL PROPERTIES OF BEND FURNITURE BOARDS (Innovation in Woodworking Industry and Engineering design, 2026)
In the manufacture of furniture structural elements from folded glued thin furniture panels, it is important to determine the parameters affecting the performance of the finished wood composite panels. The purpose of the study was to determine the effect of the type of adhesive used on laminated high-density laminated wood fiber boards (HDF) and poplar plywood. The test specimens are made of five layers of 2.8 mm thick HDF slats and 4 mm thick plywood with 260/100 mm glued plate dimensions. For bonding, three types of adhesives were used - polyvinyl acetate (PVA) dispersion adhesive Jowacoll 103.05, polyurethane (PU) dispersion adhesive - Jovapur 150.50 and polyurethane wood adhesive - SOUDAL 66A. Bending and gluing were performed in a laboratory vacuum press with a rubber membrane and a template with a radius of curvature of 150 mm. The time to achieve minimum technological adhesion strength, vacuum velocity and minimum bending radius are determined. Samples were tested by standard bending with shoulder collection. The results obtained are analyzed and presented graphically.